Field testing of different methods for monitoring mammals in Trans-Himalayas: A case study from Lahaul and Spiti - Bheem Dutt Joshi; Amira Sharief; Vineet Kumar; Manish Kumar; Ritam Dutta; Romila Devi; Ashutosh Singh; Mukesh Thakur; Lalit Kumar Sharma; Kailash Chandra (Global Ecology and Conservation, 2020)
Combined surveys based on non-invasive genetic methods and camera trapping increase chances of capturing most of the elusive species which are otherwise challenging to document, especially in high altitude areas due to tough terrains and inaccessibility. The Trans–Himalayan mountain ranges of India are neglected ecosystem in the context of faunal assessment and their monitoring. The present study provides a comparative performance of four methods i.e., line transects, camera traps and non-invasive DNA analysis in enumerating the mammalian diversity of Lahaul and Spiti (L&S) in Indian Trans Himalayan region. We undertook sign surveys, field questionnaire, camera trapping, and collected faeces (n = 471) from the trails/transects for DNA analysis. The study was conducted in seven different ranges/blocks of L&S. Together all methods resulted in the identification of 23 species of mammals with two new records, i.e. Asiatic Black bear (Ursus thibetanus) and Leopard cat (Prionailurus bengalensis) in the region. Other key species detected are Himalayan Brown bear (Ursus arctos isabellinus), Snow Leopard (Panthera uncia), Tibetian Wolf (Canis lupus). The camera traps performed best with a maximum number of species (19) than the other three methods, i.e. Questionnaire survey (16), indirect sign survey (15) and DNA based (10). However, no significant differences (Kruskal-Wallis, K = 10; P > 0.05) was observed among the methods used for species detection. The camera trap detection varied significantly among the different forest ranges (K = 12; P < 0.004). The DNA based detection aided in overcoming the issue of wrong identification of the faecal samples of closely related species. Out of 471 non-invasive samples 195 (41%) samples resulted in DNA based in species identification. Through this article, we discussed the performance of different methods in detecting mammalian diversity for developing field-tested monitoring protocol specifically for the Trans-Himalayan region. We recommend use of camera trap along with non-invasive sampling for monitoring mammals in the Trans-Himalayas. Keywords: Conservation, Trans-Himalayan ranges, Camera trapping, Non-invasive genetics, Species detection, Comparative assessments